Telkom's New Wave Valuation - Alinursafa, Ibnu; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
Telkom's share price in the Indonesian stock exchange (IDX) since 2007 growth lower comparing to the performance of the overall index. From year 2007 to the end of 2012, Telkom's share price has dropped by approximately 10%, whereas the composite stock price index increased by about 130% in the same period. The low performance of Telkom stock price due to the high of competition level in Indonesia telecommunications business. The price war reduced phone rates, and the firm face a negative growth around 7% in 5 years. To anticipate negative growth, the management has decided to enter the business of New Wave as a new revenue stream.To determine the root cause of low performance of Telkom’s share price, The analysis should be done by calculating the fundamental value of Telkom. Telkom’s fundamental share price calculated using the Free Cash Flow to Equity (FCFE) and Dividend Discount Model (DDF) method as comparison. Based on FCFE, the fair fundamental prices shares amounted Rp.11.961, while based on DDF Telkom shares process is Rp. 13, 253. This result is not much different from the Telkom closing share price 2013 amounted Rp .9,050. To increase growth is to increase the proportion of new wave business. Increase in new wave business can be done with synergies between business units and subsidiaries in the Telkom Group. The programs are conducted on a unit must have an impact to other units, in order to support the business growth of new wave. Keywords: stock, valuation